2020
DOI: 10.21203/rs.3.rs-37041/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Microorganisms and clinical outcomes of early- and late-onset ventilator-associated pneumonia at Srinagarind Hospital, a tertiary center in Northeastern Thailand

Abstract: Back ground: Ventilator-associated pneumonia (VAP) is a common nocosomial infection in intensive care unit (ICU). Local microbiological surveillance of pathogens and resistance patterns for early-onset VAP (EOVAP) and late-onset VAP (LOVAP) will help to choose appropriate empiric antibiotics. Objective: To compare the multi-drug resistant (MDR) pathogens, treatment outcomes, and factors associated with hospital mortality of VAP. Method: A cross-sectional study between 1 January 2015 and 31 December 2017 at Sri… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…A previous study found that the pathogens found in the lung were identical to those constituting endotracheal tube biofilms in 70% of VAP patients [22]. Staphylococcus aureus, Klebsiella pneumoniae, Acinetobacter baumannii and Pseudomonas aeruginosa are among the bacterial pathogens most commonly associated with VAP, particularly with late-onset disease in which multidrug-resistant strains become prevalent [23][24][25]. The fungi Candida albicans, an oral commensal and opportunistic pathogen, rarely causes VAP but frequently colonizes endotracheal tubes [20,23,26,27].…”
Section: Introductionmentioning
confidence: 99%
“…A previous study found that the pathogens found in the lung were identical to those constituting endotracheal tube biofilms in 70% of VAP patients [22]. Staphylococcus aureus, Klebsiella pneumoniae, Acinetobacter baumannii and Pseudomonas aeruginosa are among the bacterial pathogens most commonly associated with VAP, particularly with late-onset disease in which multidrug-resistant strains become prevalent [23][24][25]. The fungi Candida albicans, an oral commensal and opportunistic pathogen, rarely causes VAP but frequently colonizes endotracheal tubes [20,23,26,27].…”
Section: Introductionmentioning
confidence: 99%